Genetic mapping in phage group 2 Staphylococcus aureus. - Martin, S M (1980)
Two regimens for transformation have been devised for the phage group 2 strains UT0002-19 and UT0017 of Staphylococcus aureus. Strain UT0002-19 produces exfoliative toxin, which is responsible for the clinical manifestations of the staphylococcal scalded skin syndrome, whereas strain UT0017 does not produce exfoliative toxin. A large pool of antibiotic-resistant and auxotrophic mutants from strains UT0002-19 and UT0017 were isolated by using (i) antibiotic gradient plates, (ii) trimethoprim selection, and (iii) nitrosoguanidine mutagenesis, which sometimes was coupled by enrichment with penicillin or methicillin. Transformation frequencies of genetic markers in mutant strains ranged from 10(-6) to 10(-8). Three genetic linkage groups were identified on the strain UT0017 chromosome. The first linkage group was thy-4-lys-5-trp-21-thr-4, the second was pyr-26-nov-9-his-3, and the third consisted of ilv-9 and pen-1, a genetic determinant for beta-lactamase synthesis. Two linkage groups were detected on the strain UT0002-19 CHROMOSOMe. The first was defined as thy-1-lys-5-trp-3-thr-4-ala-8, whereas the second consisted of nov-9 and his-3 markers. A chromosomal locus that controlled synthesis of exfoliative toxin could not be mapped.